A multilevel approach for analysis and optimization of nano-enhanced composite structures. (1st November 2015) - DorMohammadi, S.; Rais-Rohani, M.; Rouhi, M.
Abstract: A hierarchical framework for multilevel analysis and design of composite material and structural systems is presented. The micro- and macro-level material models are integrated with structural analysis to evaluate the response characteristics of the loaded structure affected by both the nanofiber enhancements and continuous fiber reinforcements in the polymer matrix. Besides the nanofiber waviness, the nanofiber–matrix interphase is also included in evaluation of the homogenized stiffness properties of the matrix. To take advantage of the design features at different length scales, a multilevel optimization approach based on analytical target cascading is developed and applied to material–structural analysis and design optimization of a rectangular composite sandwich plate under in-plane loading conditions. The design variables include the volume fractions of the nanofibers and continuous fibers along with the thicknesses of the core and facesheet plies. Multiple failure modes in the form of global buckling, shear crimping, intracell buckling, and face sheet wrinkling are included as design constraints. Different edge loads are applied to study the effect of loading on optimum design. Besides the significant computational efficiency in the multilevel approach, the analysis detail and the results of the multilevel sandwich plate optimization problem are presented and discussed.